Multithreading in C♯ 5.0 cookbook: over 70 recipes to help you learn asynchronous and parallel programming with C♯ 5.0 quickly and efficiently - Agafonov, Eugene (PACKT Publishing, 2013)
This book is an easy-to-follow guide full of hands-on examples of real-world multithreading tasks. Each topic is explained and placed in context, and for the more inquisitive readers, there are also more in-depth details of the concepts used. If you are a developer or new to multithreaded programming and you are looking for a quick and easy way to get started, then this book is for you. It is assumed that you have some experience in C# and .NET already, and you should also be familiar with computer science and basic algorithms and data structure.